Tunneling field-effect transistor with Ge/In0.53Ga0.47As heterostructure as tunneling junction - Hu, Hailong. (2013)
High quality epitaxial germanium (Ge) was successfully grown on In0.53Ga0.47As substrate using a metal-organic chemical vapor deposition tool. The valence band offset ΔEV between the Ge layer and In0.53Ga0.47As determined by high-resolution x-ray photoelectron spectroscopy was found to be 0.5 ± 0.1 eV, suggesting the Ge/In0.53Ga0.47As heterojunction has a staggered band alignment at the interface. This makes the Ge/In0.53Ga0.47As heterojunction a promising tunneling junction for application in tunneling field-effect transistor (TFET). Lateral TFET with in situ doped p+ Ge-source In0.53Ga0.47As-channel using a gate-last process was demonstrated for the first time. The temperature dependence of the TFET transfer characteristics was investigated. The TFET with gate length (LG) of 8 μm exhibits an on-state tunneling current (ION) of 380 nA/μm at VGS = VDS = 2 V. The subthreshold swing (S) at the steepest part of the transfer characteristics of this device is ∼177 mV/decade. It was found that the off-state leakage current (IOFF) was determined by the Shockley-Read-Hall generation-recombination current in the Ge-source region. The temperature dependence of ION was mainly due to the change of the band gap with temperature. Furthermore, S was found to be limited by the trap-assisted tunneling at the Ge/In0.53Ga0.47As tunneling junction. The low ION and poor S can be enhanced by improving the source/channel profile and optimizing Ge epitaxial growth process.